A STUDY ON COMMUNITY TOURISM AND ITS IMPACT IN KERALA WITH SPECIAL REFERENCE TO ERNAKULAM DISTRICT - VINAY RAJ R (Journal of Exclusive Management Science, 2012)
Kerala, a state situated on the tropical Malabar Coast of south western India, is one of the most popular tourist destinations in the country. Named as one of the ten paradises of the world by the National Geographic Channel, Kerala is famous especially for its ecotourism initiatives Its unique culture and traditions, coupled with its varied demography, has made Kerala one of the most popular tourist destinations in the world. Tourism industry is a major contributor to the state's economy. Ernakulam District is a district of the state of Kerala in southern India. Ernakulam, the commercial capital of Kerala, served by an international airport, fine communication facilities, excellent accommodation, modern amenities and a lot of attractive tourist places gives a breath taking experience for its visitors and settlers. The district took its form on 1st April 1958, by carving out the areas of erstwhile Travancore, Kochi & Malabar kingdoms. The word Ernakulam was derived from a Tamil word 'Erayanarkulam' which means 'Lord Shiva's abode'. The commercial capital of Kerala and the most cosmopolitan of Kerala’s cities, Cochin is a fascinating blend of cultures. From time immemorial, it has been the favorite destination of globe-trotters and explorers.